Price Perception, Service Quality and Customer Satisfaction (Empirical Study on Cafes at Tondano City) - Tendur, Sheeren T.E Tendur; Hutabarat, Vincky Vincent; Tumbelaka, Steven S.X (AIBPM Publisher, 2021)
The problem studied in this study is the low level of customer satisfaction on cafes in Tondano city. This can be seen from there are many complaints about the slow service, and also the price offered by the cafe can be categorized as relatively expensive. Therefore, this study aims to determine whether the price and service quality variables have simultaneously significant effect on consumer satisfaction. This study used quantitative method with accidental sampling technique. The number of respondents was 150 customers, which were then tested using multiple regression analysis. The results found that price and service quality have a significant effect on consumer satisfaction, either partially or simultaneously. It can be said that affordable price and good service quality would increase customer satisfaction.